Novel Strategy to Monitor Fluid Absorption and Blood Loss during Urological Endoscopic Surgery: An Advanced Approach - Zhang, Yunxin; Fan, Ning; Zhang, Lixiu; Hu, Xuemei; Wang, Li; Wang, Hanzhang; Kaushik, Dharam; Rodriguez, Ronald; Wang, Zhiping (Issues and Development in Health Research Vol. 3, 2021)
Background: There is paucity of an optimal method to detect fluid absorption and hemorrhage during urological endoscopic surgery. We designed an endoscopic surgical monitoring system (ESMS) and estimated its performance to establish a practical instrument that can monitor the blood loss and fluid absorption accurately and non-invasively during urological endoscopic surgery. Methods: Our system employed the strain gauge transducers to detect the inflows and outflows of the irrigating solutions and the photoelectric sensor to determine the hemoglobin concentration of the collected irrigating fluid. The amount of blood lost and the volume of fluid absorbed during endoscopic surgery could be calculated by computer program. The accuracy and validity of this system were validated in simulated experiment and clinical study of 200 patients who underwent transurethral resection of the prostate (TURP). Results: The relative errors for fluid absorption detection were between 0.07% and 1.00% and the coefficient of variation in serial analysis ranged from 0.78% to 3.86%. Furthermore, the relative errors for blood loss detection were between 0.06% and 1.33% and the coefficient of variation in serial analysis ranged from 0.86% to 3.94%. In clinical study for TURP, the mean fluid absorption was 644 mL and blood loss was 238 mL. Conclusions: We provide the accuracy and validity of ESMS. It provides an early and real time detection and warning of irrigation fluid absorption and blood loss to make endoscopic surgical procedure safer for the patient.